Exploration of Seafloor Massive Sulfide Deposits with Fixed-Offset Marine Controlled Source Electromagnetic Method: Numerical Simulations and the Effects of Electrical Anisotropy - Peng, Ronghua; Han, Bo; Hu, Xiangyun (Minerals (Basel), 2020)
Seafloor massive sulfide (SMS) deposits have attracted growing interest and become the focus of current seafloor mineral exploration. One key challenge is to delineate potential SMS accumulations and estimate their quantity and quality for prospective resource mining. Recently, geophysical electromagnetic methods which are routinely used for land-based mineral exploration are being adapted to detect and assess SMS occurrences by imaging their conductivity distributions. However, the rough seafloor topography and electrical anisotropy of the seafloor formations encountered in practical surveys pose challenges for reliable data interpretation, and recent studies have revealed that the rough bathymetry could cause measurable distortions. Here, we consider a fixed-offset marine controlled-source electromagnetic method (CSEM) for SMS exploration, and investigate the effects of electrical anisotropy of sedimentary formations through numerical simulations for marine CSEM surveys aiming at conductive targets in the shallow regions of the seafloor. Numerical results demonstrate that the presence of electrical anisotropy could impose significant influence on fixed-offset marine CSEM data and suggest that the distortions should be sufficiently accounted for reliable data interpretation, thus lending confidence to subsequent quantification of available SMS minerals.